Defenisi Peran Dan Contoh Teknologi - Zachy .; Abidzar .; Farell .; Rifky .; Adit .; Said Hambali (Journal Of Informatics And Busisnes, 2026)
Information systems play a strategic role in supporting data management, information provision, and decision-making processes within organizations. Rapid developments in information technology require a clear understanding of the roles of information systems and the technologies that support their implementation. This study aims to explain the roles of information systems and to identify examples of technologies that support these roles in organizational contexts. The research adopts a descriptive qualitative approach through a literature study by reviewing relevant scientific publications related to information systems and information technology. The results indicate that information systems function as tools for data processing, information integration, and decision support, contributing to improved effectiveness and efficiency of organizational operations. Technologies such as database systems, web-based applications, and decision support systems are identified as key components that support these roles. This study is expected to provide a structured conceptual understanding of information system roles and serve as a reference for organizations and future research in the field of information systems.